PENGARUH KEBUDAYAAN ISLAM TERHADAP KEBUDAYAAN LOKAL MASYARAKAT JAWA The Influence of Islamic Culture on the Local Culture of the Javanese Community - Maulana, Sindy; Melati Simanullang, Olivia Sri; Siregar, Elly Fadilla; Aurora, Sagita Isma; Abdillah Alqahzi; Valentino Surbakti; Lukitoyo, Pristi Suhendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research explores the dynamics of acculturation between Islamic values and the local traditions of Javanese society through historical and anthropological perspectives. Focusing on the 15th and 16th-century period, the study examines how Islam did not emerge to erode well-established local cultural roots, but rather integrated through a syncretic process that gave rise to a unique new cultural identity. By employing a literature review method based on authoritative scientific sources, this study dissects cultural proselytization (dakwah) strategies particularly those of the Wali Songo in weaving Islamic nuances into architecture, performing arts, literature, and life-cycle rituals. The findings indicate that Islamic influence in Java is both transformative and adaptive; it successfully enriched the Javanese character with monotheistic (Tawhid) values without diminishing its original cultural essence.